Simple Resolution of Enantiomeric NMR Signals of α‐Amino Acids by Using Samarium(III) Nitrate With L‐Tartarate. Issue 5 (7th April 2015) - Aizawa, Sen‐Ichi; Kidani, Takahiro; Takada, Sayuri; Ofusa, Yumika
Abstract Readily available L‐tartaric acid, which is a bidentate ligand with two chiral centers forming a seven‐membered chelate ring, was applied to the chiral ligand for the chiral nuclear magnetic resonance (NMR) shift reagent of samarium(III) formed in situ. This simple method does not cause serious signal broadening in the high magnetic field. Enantiomeric 13C and 1H NMR signals and enantiotopic 1H NMR signals of α‐amino acids were successfully resolved at pH 8.0 and the 1:3 molar ratio of Sm(NO3)3:L‐tartaric acid. It is elucidated that the enantiomeric signal resolution is attributed to the anisotropic magnetic environment for the enantiomers induced by the chiral L‐tartarato samarium(III) complex rather than differences in stability of the diastereomeric substrate adducts. The present 13C NMR signal resolution was also effective for the practical simultaneous analysis of plural kinds of DL‐amino acids. Chirality 27:353–357, 2015.© 2015 Wiley Periodicals, Inc.